An alcohol-governed mechanism of monocarbonyl oligomerization: implications for explosive growth of fine particulate matter - Yuemeng Ji; Jiaxin Wang; Yongpeng Ji; Yanpeng Gao; Weina Zhang; Jiangyao Chen; Guiying Li; Taicheng An (npj Climate and Atmospheric Science)
Abstract Secondary organic aerosol (SOA), as a major component of fine particulate matter (PM2.5), significantly impacts air quality, climate, and human health. Although the aqueous chemistry of oxygenated organic compounds (OOCs) is acknowledged as an important contributor to the global SOA budget, the mechanisms by which this process yields SOA-forming oligomers remain unclear. Therefore, we clarify the aqueous-phase reactions of monocarbonyl OOCs (MOOCs, e.g., octanal and 2,4-hexadienal) in sulfuric acid aerosols using quantum chemistry and kinetic calculations. We identified all intermediates and products for established reaction pathways and explored a newly alcohol-governed mechanism for MOOC oligomerization, independent of prior atmospheric knowledge. Oligomers are yielded by the repetition of simple organic reactions, including protonation/deprotonation, hydration/dehydration, and nucleophilic addition, leading to rapid SOA formation. Our results unveil that an alcohol-governed aqueous-phase reaction mechanism of MOOC is likely prevalent across other OOCs in the atmosphere and helps to explain the explosive growth of PM2.5.